IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) PT AETRA AIR JAKARTA - Ratri Mustika Dewi; A. Rahman (Universitas Mercu Buana, 2016)
Good reputation in the eyes of Stakeholders and stakeholders in a company is something that absolutely must be done To get a good reputation a company not only enough to run its business activities but also must be supported by other activities. A good reputation for a company, one of which is closely related to the social environment in which they live. The research used a qualitative research approach that produces and processes descriptive data, such as observations, interview transcripts, field notes, and so forth. The conclusion that the program is a form of corporate awareness of the company in line with the vision and mission of the company and CSR program is considered to provide a positive value for stakeholders. This program is the first Aetra program conducted outside the service area by utilizing for